Mathematics

how do you simplify
 x-2(x+3y)-(2x+3y)-4(x+y)

can i have an explanation too!!


Answers

jbaby493

4 years ago Comment

1. Multiply x and 3y by x-2
x^2-2x (i.e. x*x=x^2, -2*x=-2x)
3yx-6y (i.e. 3y*x=3yx, 3y*2=6y)

2. Multiply x+y by -4
x*-4= -4x
y*-4=-4y

3. Multiply 2x+3y by -1
2x*-1=-2x
3y*-1=-3y

4. Combine like terms
x^2     3yx    -2x    -6y
                   -2x     -3y
                   -4x     -4y
-------------------------------------------
x^2    +3yx   -8x      -13y

Hope this helps!